Quality of Life and Cost of Illness in Patients with Hand Dermatitis: A Cross-sectional Study - Yerragangu Deepthi Chowdary; TS Rajashekar; Suresh Kumar; K Hanumanthayya; C Madhu Kiran; RE Meghana (Journal of Clinical and Diagnostic Research, 2023)
Introduction: The high incidence, severity, and chronicity of hand dermatitis can lead to a massive impact on the Quality of Life (QoL). Despite its medical and socioeconomic importance, there is a paucity of data that addresses the cost-of-illness, economic factors, and its effect on the QoL in patients with hand dermatitis. Aim: To estimate the Dermatology Life Quality Index (DLQI) and cost-of-illness in patients with hand dermatitis. Materials and Methods: This cross-sectional study was conducted in the Outpatient Department (OPD) of Dermatology at RL Jalappa Hospital and Research Centre, Kolar, Karnataka, India. The duration of the study was four months, from September 2022 to December 2022. A total of 82 subjects with the skin condition of hand dermatitis. The QoL (DLQI questionnaire) and cost-of-illness were estimated. The economic burden of hand dermatitis was measured by its direct and indirect costs. Statistical analysis was carried out using the Statistical Package for Social Sciences (SPSS) version 22.0 and the comparison was done using t-test and Analysis of Variance (ANOVA) test. Results: The mean age of the study participants was 39.76±13.30 years. Eczema was the most common hand dermatitis, seen in 47 (57.3%) patients followed by psoriasis. A total of 82 patients (34 males and 48 females). The average total cost of the illness was Indian Rupee (INR) 5725.29 per individual among all patients, with indirect costs catering to 63.75% of total costs. The average total cost of the illness was INR 6105.03 and INR 5456.31 per individual among male and female patients, with indirect costs (INR 3976.76) catering to 65.14% in males and (INR 3418.75) catering to 62.66% of total costs among females. DLQI revealed social embarrassment had a very much impact seen in 36 participants (43%) followed by disturbances in social and leisure activities seen in 23 participants (28%). Conclusion: Hand dermatitis is distressing to the patient, which can lead to poor QoL. Cost of illness studies shed light on elements, that contribute to high expenses associated with this frequently devastating condition, aiding in its treatment or prevention.